Comparison of bloodstream infections due to Corynebacterium striatum, MRSA, and MRSE - Shu-Hua He; Yan Chen; Hong-Li Sun; Shan Li; Shi-Tong Diao; Yi-Fan Wang; Zhuo-Xin He; Li Weng; Jin-Min Peng; Bin Du (BMC Infectious Diseases, 2024)
Abstract Background Corynebacterium striatum (C. striatum), a common skin and mucosal colonizer, is increasingly considered as an opportunistic pathogen causing bloodstream infections (BSIs). This study aims to investigate the clinical features and outcomes of C. striatum-BSI. Methods We included hospitalized cases with C. striatum-positive blood cultures from January 2014 to June 2022 and classified them into C. striatum-BSI group and contamination group; Clinical characteristics, treatments, and outcomes were compared between the C. striatum-BSI group and contamination group, Methicillin-resistant Staphylococcus aureus (MRSA)-BSI and Methicillin-resistant Staphylococcus epidermidis (MRSE)-BSI. Results Fifty-three patients with positive C. striatum blood cultures were identified. Among them, 25 patients were classified as C. striatum-BSI, with 21 as contamination cases. And 62 cases of MRSA-BSI and 44 cases of MRSE-BSI were identified. Compared to the contaminated group, the C. striatum-BSI group had a shorter time to positivity of blood cultures (27.0 h vs. 42.5 h, P = 0.011). C. striatum-BSI group had a longer time to positivity (27 h) when compared to both the MRSA (20 h) and MRSE groups (19 h) (p < 0.05). Appropriate therapy within 24 h of BSI onset was significantly lower in the C. striatum group (28%) compared to the MRSA (64.5%) and MRSE (65.9%) groups (p < 0.005). The 28-day mortality was higher in the C. striatum group (52.0%) compared to the MRSA (25.8%) and MRSE (18.2%) groups.  Conclusions Given the distinct characteristics of C. striatum-BSI, including a longer time to positivity than other Gram-positive bacteria and higher mortality rates, we suggest prescribing early appropriate antibiotics if C. striatum-BSI is suspected.